An automation tool for exporting structure models from Revit to Tekla Structure. Issue 4 (March 2021) - Ma, Jie; Ding, Siwen; Zhang, Dehai; Li, Yue
Abstract: BIM modeling process currently faces a significant exchange issues since there is a need for conversion of intelligent building models between various design applications. Right now, Autodesk Revit and Tekla Structures, as the most popular BIM applications, in which compatibility issues were noted since many projects are facing the difficulties when a building model was converted from Revit to Tekla. Although Industrial Foundation Class (IFC), as a promise open file format which enables the possibility of exchange of models between different design applications, an exchange of models with IFC may cause compatibility issues where parts of building information can be lost or relocated. This study aims to develop a plug-in application for converting building models from Revit to Tekla by using API interface. To test the plug-in tool, a 34-storey high-rise residential building model is exchanged from Revit and Tekla with IFC and the plug-in application. The results showed the plug-in application performed better than IFC method in terms of accuracy and efficiency.